Pathogenic variability of Pyricularia grisea from the high- and mid-elevation zones of Bhutan - Thinlay; Zeigler, R.S.; Finckh, M.R. (Scientific Societies, 2000)
Thirty isolates of P. griseacollected from rice during a blast epidemic in 1995 in the high (1,800 to 2,600 m) and middle (1,200 to 1,800 m) elevations of Bhutan and 80 isolates collected from one rice cultivar from two high- and two mid-elevation sites in 1996 were analyzed for virulence. Differential varieties were indica CO39, with five near-isogenic lines (NILs) for resistance genes in the genetic background of CO39, and japonica Lijiangxintuanheigu (LTH), with five NILs for LTH. Twelve selected Bhutanese landraces also were studied. In addition, 10 blast nurseries consisting of the NIL sets, important local landraces, and representatives of international differential groups were established in the 1996 and 1997 growing seasons in the mid- and high-elevation agroecological zones. The 110 isolates were differentiated into 53 pathotypes based on the 2 NIL sets. Thirteen isolates were avirulent on all of the NILs but were compatible with some landraces. Several isolates were able to attack one of the NILs of CO39 but not CO39. These results strongly suggest that both CO39 and LTH possess previously unidentified resistance. The landraces were not uniform in their reactions to the isolates. When a reaction index taking into account all individual plant reactions was used, isolates that had been assigned to the same pathotype could be further differentiated, indicating that the NIL sets could not completely discriminate virulences in Bhutanese P. grisea populations. In the trap nurseries, disease was always present in the middle elevations, but disease was very low during July 1996 in the high elevations and only present during August and September 1997. Almost all varietal groups were more frequently attacked in the middle than in the high elevations, indicating that the virulence spectrum is wider and the conduciveness of the environment is greater in the middle elevations. Landraces from the high elevations were most susceptible, followed by international differential groups 7 and 8. The results suggest that selection has yielded landraces with more complete and complex resistance in the more disease-conducive mid-elevation environment. At the same time, the pathogen population also possesses a wider virulence spectrum in that environment.